Rendimento e classificação das lâminas de Eucalyptus grandis W. Hill utilizando dois tratamentos térmicos - Coneglian, Ademilson; Severo, Elias Taylor Durgante [UNESP]; Batista, Wagner Roberto; Pereira, Ismael Martins; da Silvas Gomes, Ivana (My University, 2017)
This study aims to verify the influence of thermal treatments (water and steam of à 85°C ) in the yield and final classification of Eucalyptus grandis sheets. Six trees, obtaining a total of thirty logs adequate for lamination, with diameters of 25-40 cm. The average yield of Eucalyptus grandis lamination process was of 38.43% for steam heated logs, and 24.31% for water heated logs, with a significant difference at 5% probability. Wood sheets from Eucalyptus grandis have shown viability for plywood manufacturing in both treatments, therefore, it is recommended to use indirect heating with steam for a lower incidence of top cracks, and consequently higher lamination yield.
Yield and classification of Eucalyptus grandis W. Hill sheets using two thermal treatments
Keywords: Hot water; Lamination; Steam heating